The Impact of Regulatory Changes on the Information Content of Target Prices - Petrou, Zacharias; Charitou, Andreas; Karamanou, Irene; Landsman, Wayne (My University, 2025)
We document a significant increase in the reliability of target prices following the implementation of SRO rulings, which were designed to mitigate sell-side analyst conflicts of interest. We test whether the increase is associated with the implementation of the rules’ provisions (the regulation effect) or the concurrent migration of most brokerages to three-tier rating systems (the tier effect) by examining differences in the informativeness, optimism, and accuracy of target prices issued with and without recommendations and by utilizing periods before and after the date each brokerage changed to the new tier system. We find evidence in support of the regulation effect but no evidence in support of the tier effect. Our study contributes to the literature on SRO rulings and can help inform regulators as they evaluate the efficacy of past rules in improving the functioning of capital markets.
Keywords: analysts; target prices; recommendations; rating systems; SRO rules